Combination of antibiotics, gastric lavage and nasojejunal feeding—an effective alternative for the management of acute phlegmonous gastritis: a case report. Issue 2 (February 2021) - Wang, Jiwei; Zhang, Tao; Zhou, Xin; Huang, Handong; Wang, Maijian; Xie, Ming
Background: Phlegmonous gastritis is a rare bacterial infection of the gastric wall, characterised by purulent inflammation of the gastric mucosa, submucosa and muscularis layers. Phlegmonous gastritis has a high mortality rate, even with correct diagnosis and antimicrobial therapy. Case presentation: A 22-year-old man presented for acute epigastric pain associated with aqueous diarrhoea, vomiting and sustained fever. Abdominal computed tomography showed diffuse oedema and thickened gastric wall, increased number and size of abdominal lymph nodes and the absence of pneumoperitoneum. Fibregastroscopy revealed oedematous, ridged and thickened gastric mucosa with abundant purulent secretion, especially in the antrum, consistent with phlegmonous gastritis, which was confirmed by histological evaluation of gastric biopsies. Cultures of the tissue biopsies and purulent secretion were positive for Enterococcus cecorum . He was treated with sensitive antibiotics according to the antibiogram, and importantly, with continuous gastric lavage and individualised nutritional support therapy. He eventually recovered well and was discharged with no abdominal symptoms. Conclusions: Our case indicates that early diagnosis and immediate treatment are crucial to achieve positive outcomes. The combination of sensitive antibiotics, gastric lavage and early enteral nutrition via nasojejunal feeding might be an effective alternative for the comprehensive treatment of acute phlegmonous gastritis.